Strength and jumping performance in youth athletes: do sport specialization and age categories affect strength asymmetry? - Kalata, M.; Williams, C. A.; Verbruggen, F. F.; De Ste Croix, M.; Lehnert, M.; Zahalka, F.; Maly, T. (Research in Sports Medicine, 2025)
The aim of the study was to determine the influence of sports specialization and age on isokinetic strength, vertical jump performance and strength asymmetry in elite youth athletes.